PERUBAHAN SOSIAL MASYARAKAT PEDESAAN DI ERA TEKNOLOGI - Sardjana Orba Manullang (Cross-border, 2021)
Rural communities are known as people who are still thick with local cultural values, but along with the changing times, the paradigm has changed. The study of this study used a literature review by collecting literature related to the study and an analysis was carried out to look for findings in the study. The findings of this study looked at the condition of rural communities when the presence of internet technology had eliminated the boundaries between the differences between urban and rural communities.